P29 Bristol interstitial lung disease (BILD) service experience: BILDing on the MDT. (12th November 2015) - Sharp, C; Edwards, A; Mayers, L; Lamb, H; Barrett, S; Bhatt, N; Chandratreya, L; Darby, M; Edey, A; Millar, AB; Adamali, H
Abstract : Introduction: The weekly Bristol Interstitial Lung Disease (BILD) multidisciplinary team (MDT) meeting decides consensus diagnoses for patients from around the South West. A database records cases at the time of discussion. Referrals have increased since the advent of novel agents for Idiopathic Pulmonary Fibrosis, prompting this retrospective review of the MDT experience. Aims: Establish the range of cases referred, determining the proportion for whom MDT discussion leads to changes in diagnosis and which variables influence this. Examine IPF patients, identifying differences between those prescribed Pirfenidone or otherwise. Methods: For all cases recorded in the MDT database between 1/1/2013 and 1/1/2015, the pre-MDT differential diagnosis and consensus diagnosis, dates of referral/discussion, referral source, demographics, investigation results, the number of discussions and dispensing of Pirfenidone were reviewed. For patients with multiple entries, initial differential diagnoses were compared to final consensus. Outcome measures of interest were change in diagnosis and decision to use Pirfenidone in IPF patients. Results: 846 discussions occurred (651 individual patients) over this period. Pre/post MDT diagnoses are shown in the Table 1 . 78% of cases were discussed within 2 weeks of referral. 25% were discussed more than once (range 1–5). 54.7% of IPF cases were external referrals vs 32.3% overall. Diagnosis changed following discussion for 44.1% of patients. Pre-MDT diagnosis of IPF changed for 36.7%. Logistic regression suggests pre-MDT differential diagnosis and age at referral are main influences on change in diagnosis. Overall mean age was 65.5 years (17–91), 58.1% male. For IPF cases, mean age was 74.4 years, 76.9% male. Pirfenidone was prescribed to 46.2% of IPF cases; median time to dispensing 61 days. 6MWD was greater where Pirfenidone was given (284 m vs 249 m, p = 0.03); however lung function and HRCT pattern did not differ. 12-month mortality was 6.7% in the Pirfenidone group, 27.1% where not given (p = 0.002). Conclusion: Specialist MDT discussion influenced changes in diagnosis in 44.2% of patients. The majority of IPF cases discussed are external referrals. This has implications for design and delivery of specialist ILD services. Case selection for Pirfenidone does not appear based on lung function differences. This has implications for guidelines for its use.